Analyse of stress tolerance among exercising and non-exercising home makers (International Journal of Psychosocial Rehabilitation, 2020)
This study tried to Analyse of stress tolerance among exercise and non-exercise home makers of Cuddalore district of TamilNadu, India. For this study 30 home makers were carefully chosen as subjects in which Group-1 with 15 subjects acted as Exercise practicing group (EPG) and Group -2 with 15 subjects acted as Non exercise practice group (NEPG). Regular exercise was given for group -1 for 4 days a week for a period of 6months and group-2 did not participate in any exercise. The tool to measure stress tolerance was Reshmy and Sam Sananda Raj (1999) Stress tolerance scale. Before commencement of the training retro and after the training retro the data was collected from the respondent in stress tolerance. And the data collected has been analysed through t- test. The outcome of the research exposed that there was significant modification appeared between group -1(EPG) and group-2(NEPG), because of regular exercise tolerance towards stress was enhanced among home makers of EPG group.